Active multi-point microrheology of cytoskeletal networks - Paust, Tobias; Neckernuss, Tobias; Mertens, Lina Katinka; Martin, Ines; Beil, Michael; Walther, Paul; Schimmel, Thomas; Marti, Othmar (Beilstein Journal of Nanotechnology, 2016)
Active microrheology is a valuable tool to determine viscoelastic properties of polymer networks. Observing the response of the beads to the excitation of a reference leads to dynamic and morphological information of the material. In this work we present an expansion of the well-known active two-point microrheology. By measuring the response of multiple particles in a viscoelastic medium in response to the excitation of a reference particle, we are able to determine the force propagation in the polymer network. For this purpose a lock-in technique is established that allows for extraction of the periodical motion of embedded beads. To exert a sinusoidal motion onto the reference bead an optical tweezers setup in combination with a microscope is used to investigate the motion of the response beads. From the lock-in data the so called transfer tensor can be calculated, which is a direct measure for the ability of the network to transmit mechanical forces. We also take a closer look at the influence of noise on lock-in measurements and state some simple rules for improving the signal-to-noise ratio.
Keywords: cytoskeleton; intermediate filaments; lock-in technique; microrheology; optical tweezers